Antifungal potential of lipopeptides produced by the Bacillus siamensis Sh420 strain against Fusarium graminearum - Sarfaraz Hussain; Bowen Tai; Maratab Ali; Israt Jahan; Suha Sakina; Gang Wang; Xinlong Zhang; Yixuan Yin; Fuguo Xing (Microbiology Spectrum, 2024)
ABSTRACTBiological control is a more sustainable and environmentally friendly alternative to chemical fungicides for controlling Fusarium spp. infestations. In this work, Bacillus siamensis Sh420 isolated from wheat rhizosphere showed a high antifungal activity against Fusarium graminearum as a secure substitute for fungicides. Sh420 was identified as B. siamensis using phenotypic evaluation and 16S rDNA gene sequence analysis. An in vitro antagonistic study showed that Sh420’s lipopeptide (LP) extract exhibited strong antifungal properties and effectively combated F. graminearum. Meanwhile, lipopeptides have the ability to decrease ergosterol content, which has an impact on the overall structure and stability of the plasma membrane. The PCR-based screening revealed the presence of antifungal LP biosynthetic genes in this strain’s genomic DNA. In the crude LP extract of Sh420, we were able to discover several LPs such as bacillomycin, iturins, fengycin, and surfactins using ultra-high-performance liquid chromatography–quadrupole time-of-flight mass spectrometry. Microscopic investigations (fluorescent/transmission electron microscopy) revealed deformities and alterations in the morphology of the phytopathogen upon interaction with LPs. Sh420 LPs have been shown in grape tests to be effective against F. graminearum infection and to stimulate antioxidant activity in fruits by avoiding rust and gray lesions. The overall findings of this study highlight the potential of Sh420 lipopeptides as an effective biological control agent against F. graminearum infestations.IMPORTANCEThis study addresses the potential of lipopeptide (LP) extracts obtained from the strain identified as Bacillus siamensis Sh420. This Sh420 isolate acts as a crucial player in providing a sustainable and environmentally friendly alternative to chemical fungicides for suppressing Fusarium graminearum phytopathogen. Moreover, these LPs can reduce ergosterol content in the phytopathogen influencing the overall structure and stability of its plasma membrane. PCR screening provided confirmation regarding the existence of genes responsible for biosynthesizing antifungal LPs in the genomic DNA of Sh420. Several antibiotic lipopeptide compounds were identified from this bacterial crude extract using ultra-high-performance liquid chromatography–quadrupole time-of-flight mass spectrometry. Microscopic investigations revealed deformities and alterations in the morphology of F. graminearum upon interaction with LPs. Furthermore, studies on fruit demonstrated the efficacy of Sh420 LPs in mitigating F. graminearum infection and stimulating antioxidant activity in fruits, preventing rust and gray lesions.